Analise do cártamo como cultura enérgica - Oliveira, Christian Valcir Kniphoff de (2016)
The society turns its eyes to the future and what seems to be pleseant. Global warming and pollution are recurring issues in all meetings of international summits, because the world is seeking a new way to get their main energy demands and / or natural resources. The exchange of the current energy matrix will not be made in one day, the initiatives has been showing gradually, photovoltaic panels, wind turbines and biofuels seem to wave to a less catastrophic future. However, it is necessary to develop, seek for new sources and crops that have higher efficiency, lower cycle, higher yield and other characteristics. To this end, sometimes the History has shown that in order to find solutions for the future we need to look to the past. So millenarian crops has been proven effective nowadays. One of these crops is Safflower (Carthamus tinctorius L), a millenary plant that used to be an oil and pigment source and which will now be adopted as an object of study. Within this context, this work is organized in two research fronts and the first one is to evaluate the effectiveness of a safflower byproduct and its use in animal feed, and the second one is to evaluate the effectiveness of safflower oil as a possible source of bio-fuel by the transesterification method. The expected contribution is the seal of safflower use and its by-products as candidates for agricultural frontier expansion in Brazil's energy oil production. The intent is to alter the concentration of the traditional diet with addition of safflower meal, which is obtained by cold extrusion grain of 0.5, 10, 15 and 20% order, with a concentration in each sample triplicated in a total of 15 samples. This first step is to analyze the effectiveness of animal growth with the addition of this element in the standard feed. After this first check, there is a new verification phase from the oil generated by the extrusion of safflower. This step is to evaluate the safflower oil as a possible source for the production of bio-fuel by the transesterification method. Analysis of factors, such as viscosity, will be made, calorific value, acid value, free fatty acids and peroxides indexes fall on standards set by the National Petroleum Agency. Understanding it if it is a candidate for the agricultural frontier expansion in Brazil's energy production of oil.